2013
DOI: 10.3389/fnhum.2013.00411
|View full text |Cite
|
Sign up to set email alerts
|

Visual mismatch negativity in the dorsal stream is independent of concurrent visual task difficulty

Abstract: The manipulation of attention can produce mismatch negativity-like components that are not necessarily connected to the unintentional sensory registration of the violation of probability-based regularity. For clinical purposes, attentional bias should be quantified because it can vary substantially among subjects and can decrease the specificity of the examination. This experiment targets the role of attention in the generation of visual mismatch negativity (vMMN). The visual regularity was generated by a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…For example, previous studies have consistently shown that manipulation of the task load does not significantly influence visual MMN elicitation per se (Heslenfeld, 2003;Kremláček et al, 2013;Pazo-Alvarez et al, 2004a), although the latency of visual MMN can be slightly affected (Kimura and Takeda, 2013). This strongly suggests that predictive processes underlying visual MMN elicitation can operate automatically without substantial attentional requirements.…”
Section: Top-down Control Over the Mmn-generating Processes In The VImentioning
confidence: 96%
“…For example, previous studies have consistently shown that manipulation of the task load does not significantly influence visual MMN elicitation per se (Heslenfeld, 2003;Kremláček et al, 2013;Pazo-Alvarez et al, 2004a), although the latency of visual MMN can be slightly affected (Kimura and Takeda, 2013). This strongly suggests that predictive processes underlying visual MMN elicitation can operate automatically without substantial attentional requirements.…”
Section: Top-down Control Over the Mmn-generating Processes In The VImentioning
confidence: 96%
“…That is, when we attend to or are conscious of something other than the blinking indicator light, such as a pedestrian crossing the road or a song on the car stereo, generative models for the blinking light continue to be established, tested, and updated. Although there is plenty of evidence showing that vMMN occurs in the absence of attention to the standards and deviants (Berti, 2011;Heslenfeld, 2002;Kimura & Takeda, 2013;Kreml aček et al, 2013;Kuldkepp, Kreegipuu, Raidvee, N€ a€ at€ anen, & Allik, 2013;Pazo-Alvarez, Amenedo, & Cadaveira, 2004; for reviews, see Czigler, 2007;Stefanics et al, 2014), to the best of our knowledge, there is no evidence showing that vMMN occurs in the absence of consciousness of those stimuli: previous attempts have failed either to elicit a vMMN from stimuli that are not perceived (Czigler, Weisz, & Winkler, 2007;Flynn, Liasis, Gardner, & Towell, 2016;Meng et al, 2015) or to hide their stimuli from consciousness (Jack et al, 2015;Kogai, Aoyama, Amano, & Takeda, 2011;van Rhijn, Roeber, & O'Shea, 2013). In the experiment we report here, we sought to provide that evidence.…”
mentioning
confidence: 99%
“…Kremláček et al (2013) presented subjects with radial motion stimuli in the periphery of the visual field using an oddball paradigm and manipulated the attentional load by varying the difficulty of a central distractor tasks. They aimed to manipulate the amount of available attentional resources that might have been involuntarily captured by the vMMN-evoking stimuli presented in the periphery outside of the attentional focus.…”
mentioning
confidence: 99%